2013
DOI: 10.1111/jir.12007
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between flat foot condition and gait pattern alterations in children with Down syndrome

Abstract: Children with flat foot displayed a less functional gait pattern in terms of ankle kinetics than children without flat foot, suggesting that the presence of flat foot may lead to a weaker efficient walking. Then, the increasing flat foot tended to result in lower push-off ability, leading to a less functional walking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 29 publications
4
43
0
2
Order By: Relevance
“…All studies reported measures of variability and intention to treat analysis; more than 85% reported follow-up and intra-group analysis. The therapists were not blind in any study, while two of the studies reported blinding of the participants 14,35) .…”
Section: Resultsmentioning
confidence: 99%
“…All studies reported measures of variability and intention to treat analysis; more than 85% reported follow-up and intra-group analysis. The therapists were not blind in any study, while two of the studies reported blinding of the participants 14,35) .…”
Section: Resultsmentioning
confidence: 99%
“…Other musculoskeletal abnormalities include dislocation/subluxation of the patella, deformities such as genu valgum, pes planus, metatarsus primus varus, and scoliosis (Diamond et al, ; Yam et al, ), all of which have been attributed to ligament laxity (Galli et al, ). In addition, brachycephaly, brachydactyly, wide hands, fifth finger clinodactyly, increased web space between the great and second toes, and short stature have been documented as possible morphological changes (Roizen and Patterson, ).…”
Section: Clinical Features Of Dsmentioning
confidence: 99%
“…DS is primarily characterised by variable intellectual disability, distinct facial phenotype, short stature, generalised joint laxity and hypotonia [2,3]. Physical disability is an additional problem in people with DS and manifests as reduced physical fitness [4], reduced lower limb muscle strength [5], less functional gait patterns [6] and gait instability [7]. …”
Section: Introductionmentioning
confidence: 99%